Liberté, Égalité, Animalité: Human–Animal Comparisons in Law†. Issue 1 (10th February 2016) - Peters, Anne
Abstract: This article problematizes the discrepancy between the wealth of international law serving human needs and rights and the international regulatory deficit concerning animal welfare and animal rights. It suggests that, in the face of scientific evidence, the legal human–animal boundary (as manifest notably in the denial of rights to animals) needs to be properly justified. Unmasking the (to some extent) 'imagined' nature of the human–animal boundary, and shedding light on the persistence of human–animal comparisons for pernicious and beneficial purposes of the law, can offer inspirations for legal reform in the field of animal welfare and even animal rights.